Avaliação Econômica da remuneração de Usinas Fotovoltaicas em Geração Distribuída na modalidade de Autoconsumo Remoto - Bavaresco, Lincon Pieter (2022)
The implementation of photovoltaic plants is a widespread alternative in the search for savings in energy bills. The leasing of plants is an option that has emerged in this market. In this context, this work makes a general approach to Distributed Generation in the country and the modalities of energy compensation through the review of the current legislation of this sector. Depending on the modality adopted and the size of the plant, the enterprise may have different taxation costs. Thus, this work aims to survey the cost of implementing photovoltaic plants of 3 different sizes, 30kW, 300kW and 3.000kW, and to evaluate the economic viability of these plants when they are remunerated by 2 different types of consumers: consumers of the group B3 and A4 group consumers. In the simulations, it was found that the implementation costs of each plant and the interest rate of the projects greatly influence the return on investment. The 30kW plant, when remunerated by a consumer of the B3 group who pays 0.83R$/kWh, presented better economic viability when simultaneously evaluated some economic indicators such as the NPV (Net Present Value) that reached 60% greater than the value of the enterprise; the Payback that took 6 years; the IRR (Internal Return Rate) that was 23%, in witch its AMT (Atractivity Minimun Rate) was 7% and the LCOE (Levelized Cost Of Ennergy) at a cost of 0.313 R$/kWh.